Characterization of Bioethanol from Tuber of Porang Waste Fermented with Saccharomyces cerevisiae Enzyme: Effect of Fermentation Time and Yeast Ratio - Ridara, Rina; Muhammad, Muhammad; Setiawan, Adi; Riskina, Shafira; Nurjannah, Siti (Jurnal Teknik Kimia dan Lingkungan, 2023)
The production of bioethanol from non-plant lignocellulosic materials has reached a commercial scale and is advocated as a possible solution for the decarbonization of the transport sector. Porang pulp tubers can be converted into bioethanol because they have abundant potential due to their high glucomannan content. The purpose of this study was to determine the effect of fermentation time and the ratio of yeast addition on bioethanol production. The methods used are hydrolysis, fermentation and distillation methods. The hydrolysis process used 5% (v/v) HCl catalyst, the fermentation process with 6 gr sample powder tuber of waste used Saccharomyces cerevisiae bacteria with varying ratios of 2.5, 4 and 6.5 g and variations in fermentation time for 2, 4 and 6 days at 38-40˚C. The results showed that the duration of fermentation had a significant effect on the yield of bioethanol, where microorganisms have the opportunity to break down more glucose to produce bioethanol. While the ratio of the addition of yeast added to the fermentation process, the greater the ratio of the addition of yeast, the greater the bioethanol produced. Where the addition of 6.5 grams of yeast and 6 days of fermentation time, resulted in a yield of 9.889%, a bioethanol concentration of 37.599%, a refractive index of 1.3642 and a density of 1.04 g/ml.